อุบัติการณ์และปัจจัยที่เกี่ยวข้องกับการบาดเจ็บจากลิง ของคนท้องถิ่นและนักท่องเที่ยวในอำเภอเมือง จังหวัดลพบุรี ระหว่างปี พ.ศ. 2556-2560 - อโณทัย จัตุพร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Background: Conflicts between monkey and human were increasing, because of urbanization and deforestation. Muang district of Lopburi is one of the greatest conflict areas in Thailand, where public health concerned of zoonoses transmission from monkey bites and scratches was high. Currently, there is no epidemiological research of monkey related injury in Thailand.Objective: 1) To determine incidence of monkey related injury, 2) To illustrate trend of the incidences, and 3) To describe characteristics of the injured cases in Meuang district, Lopburi province, during 2013-2017.Methods: A cross-sectional analytical study was conducted to compare monkey related injury, in terms of cumulative incidences, between locals, Thai, and foreign tourists by collecting secondary data from hospital medical records in the study area. The cumulative incidences were used to calculate relative risk between the tourists and the locals. Trend was presented by line graph. Characteristic of the injury cases was presented by frequency and percentage.Results: Yearly incidences of locals, Thai, and foreign tourist were in range of 9.16 - 18.33, 190.16 - 379.13, and 254.07 – 736.91 per 100 000 population, respectively. Trend of injury was remarkably increased in foreign tourists. Recently, in 2016-2017, Thai and foreign tourists had relative risks of injury estimated to be 20 and 40 times compared to locals, respectively. Time place and circumstance of injury, and wound site suggested monkey provisioning with food as a main risk factor of monkey related injury.Conclusion: The incidences of monkey related injury was highest in foreign tourists, followed by Thai tourists. Preventive measures should primarily focus on the tourists, such as training on safety behaviors with monkey, promoting pre- and post-exposure prophylaxis, and providing safeguards, warning signs, first aids stations at monkey provisioning sites.